Confined Metal Sulfides Nanoparticles into Porous Carbon Nanosheets with Surface‐Controlled Reactions for Fast and Stable Lithium‐Ion Batteries. Issue 17 (30th August 2019) - Sun, Dongfei; Wang, Li; Li, Yanli; Yang, Yaoxia; Zhou, Xiaozhong; Ma, Guofu; Lei, Ziqiang
Abstract: To achieve high‐performance lithium‐ion batteries (LIBs), the ion diffusion behavior in electrode materials is a challenging issue. Herein, 2D FeS/porous carbon nanosheets (FeS@PCSs) hybrids were successfully prepared by a facile, low‐cost strategy involving metal salt‐assisted chemical vapor deposition (CVD) and in situsulfuration process. The unique 2D structure is conducive to shorten the ion diffusion distance, buffer the volume change of FeS nanoparticles, as well as provide abundant sites for Li + storage. Benefiting from the unique structure, the FeS@PCSs electrode exhibits high surface reaction contributions. When investigated as an anode for lithium‐ion batteries, the as‐prepared FeS@PCSs electrode exhibits a high reversible capacity (1026.2 mAh g −1 at 0.1 A g −1 ), excellent rate capability (647.2 mAh g −1 at 5 A g −1 and 561.1 mAh g −1 at 10 A g −1 ), and outstanding cycling stability (888.7 mAh g −1 at 1.0 A g −1 over 800 cycles). This work provides a cost‐effective and scalable route to synthesis the 2D carbon‐based transition metal compounds as high‐performance LIBs anodes. Abstract : A universal strategy : 2D FeS/porous carbon nanosheets are prepared by facile, low‐cost, and scalable strategy without using any template. The composite with abundant mesoporous and high surface‐exposed structure exhibits high capacity, excellent rate performance, and long cycle‐life in lithium‐ion batteries.